Plastic Waste Reduction Campaign at the Traditional Market in Nyanggelan Village, Panjer, Denpasar - SAPUTRA, Komang Adi Kurniawan; EKAJAYAINT, L.G.P. Sri; SURIANI, Ni Nyoman (Indonesia Strategic Sustainability, 2024)
This article raises the theme of a campaign to reduce plastic waste at the traditional market in Nyanggelan Village, Panjer, Denpasar. The increasing problem of plastic waste is a severe environmental challenge, especially in areas with high trading activity, such as traditional markets. Through a participatory approach, this campaign aims to increase public and trader awareness about the negative impacts of plastic waste and the importance of good waste management. Activities include outreach, counseling and training on using environmentally friendly materials as an alternative to plastic. This campaign also involves collaboration with the government and local organizations to create sustainable solutions. The results of this activity show an increase in public understanding regarding the importance of reducing plastic use and changing behavior in choosing more environmentally friendly packaging. Through this effort, Nyanggelan Village can become an example for other regions in reducing the negative impact of plastic waste and encouraging further action in maintaining environmental cleanliness and sustainability.